Issue of Helpers and Analytical Form - Begimkulova Sevara Fakhriddinovna (Zien Journals, 2023)
In linguistics, auxiliary word groups, double and repeated words, auxiliary verbs are related to the formation of forms, which have an additional meaning in the case of a combination, but in the word formation system o There are unstudied compounds that are composed of the joining of two words, but have no relation to lexicology or syntax, which require separate study in linguistics. All of this can be used as an example of the formation of an analytical form in general. In this article, the issue of analytical form in linguistics is analyzed.
Keywords: form formation; analytical form; synthetic form; grammatical meaning